Influence of relief conditions on plant growth and developmen - Nazarenko, Mykola; Назаренко, Микола Миколайович; Lykholat, Yury; Лихолат, Юрій (Дніпровський національний університет імені Олеся Гончара Геолого-географічний факультет, 2018)
The objectives of our investigations are to describe the limits of variability of the main agricultural types of modern ukrainian winter wheat varieties in order to their relations with difference growth conditions. The most target traits for determining these relations are agronomic-value, such as yield, protein content and protein composition (amount of gliadins and glutenins). As an additional purpose we evaluated relations between relief conditions and amount of microelements and heavy metals, relation amid growth conditions and content of value microelements (nitrogen, phosphorus, potassium). Our investigations confirmed statements about relations between content of nutrient elements in winter wheat plants, their uptaking from soil, type of relief, wheat variety genotype and limits of adaptable for difference conditions. Winter wheat is an cultivar with wide, but specific demands to growth and development conditions. Due to relief conditions, north exposition of the slope gives more advantages for winter wheat vegetation. We recommended varieties Komerciyna, Smuglyanka, Zolotokolosa for growing under these conditions by grain productivity and varieties Komerciyna, Smuglyanka and Natalka by grain protein content and protein composition. Variability of agriculture-value traits between varieties was higher under slope conditions than on flat. Only variety Korisna was stable by protein composition under every condition. At the same time all varieties were depended on grows conditions (relief) to reach high level of grain yield. We cannot observe just the same by grain quality. We established that wheat grains contains more microelements than straw. At the same time the lead and nickel uptake was more in the straw samples. Thus, influence of relief on microelements and heavy metals content in the winter wheat grain and straw is not so high as for macroelements and, thus, for grain productivity and quality. Мета досліджень описати межі мінливості основних сі льськогосподарських типів сучасних українських сортів пшениці озимої відповідно до їх взаємовідношень із різними умовами вирощування. Цільовими ознаками для визначення цих зв’язків були агрономічно-цінні, такі як урожайність, вміст білка та білкові компоненти (вміст гліадинів та глютенінів). Додатково оцінювали зв'язок між умовами рельєфу та вмістом мікроелементів та важких металів, зв'язок між умовами вирощування та вмістом цінних мікроелементів (азот, фосфор, калій). Наші до слідження підтвердили положення про зв'язок між умі стом поживних речовин у рослинах пшениці озимої, їх надходженням із ґрунту, типом рельєфу, генотипом пшениці озимої та межами адаптивності в різних умовах. Пшениця озима проявила себе як культура з достатньо широкими, але разом із тим специфічними вимогами до умов росту та розвитку. Відносно до умов рельєфу, схили північної експозиції мають більше переваг для вегетації пшениці озимої. Ми рекомендуємо сорти Комерційна, Смуглянка, Золотоколоса для вирощування в таких умовах за зерновою продуктивністю та сорти Комерційна, Смуглянка, Золотоколоса за вмістом білка та співвідношенням білкових компонентів. Мінливість агрономічно-цінних ознак була більш високою в умовах схилів, ніж на рівнині. Тільки сорт Корисна був стабільним у прояві ознаки композиції білків у будь-яких умовах. У той же час для досягнення більш високого рівня зернової продуктивності всі сорти сильно залежали від умов вирощування (рельєф). Щодо якості зерна такої залежності не спостерігалось. Ми встановили, що зерно пшениці містить більш високу кількість мікроелементів, ніж солома. В той же час у соломув суттєво більшій кількості надходять свинець та нікель. Таким чином, вплив рельєфу на вміст мікроелементів та важких металів не такий високий, як для макроелементів та, через них, на зернову продуктивність та якість.
Вплив умов рельєфу на ріст та розвиток рослин
Keywords: relief; рельеф; landscape; умови вирощування; winter wheat; озима пшениця